PERAN LEARNING ORGANIZATION DALAM MENIGKATKAN KINERJA PEGAWAI BADAN PUSAT STATISTIK KABUPATEN DELI SERDANG - Dika Hidayati; Sari Wulandari (JURNAL MUTIARA MANAJEMEN, 2022)
Human resources are considered as dynamic resources. Performance is a very important element in the progress of an organization. The purpose of this study was to determine the role of learning organizations in improving the performance of employees of the Central Bureau of Statistics of Deli Serdang Regency. This type of descriptive research with a qualitative approach is used in this study. The population and sample are employees of the Central Statistics Agency, Deli Serdang Regency. The data analysis technique used is descriptive qualitative method. Researchers obtained data through interviews with employees. The results showed that education had a positive effect on the performance of the Central Bureau of Statistics of Deli Serdang district because of the training and assistance to improve employee performance. This study explains that the role of highly skilled organizations will improve employee performance.